2018
DOI: 10.3389/fnins.2018.00732
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Confers Differing Effects on Neurite Outgrowth in Separate Populations of Cultured Dorsal Root Ganglion Neurons: The Role of the Insulin Receptor

Abstract: Apart from its pivotal role in the regulation of carbohydrate metabolism, insulin exerts important neurotrophic and neuromodulator effects on dorsal root ganglion (DRG) neurons. The neurite outgrowth-promoting effect is one of the salient features of insulin’s action on cultured DRG neurons. Although it has been established that a significant population of DRG neurons express the insulin receptor (InsR), the significance of InsR expression and the chemical phenotype of DRG neurons in relation to the neurite ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 54 publications
4
20
0
Order By: Relevance
“…; Lázár et al . ). Hence, because small DRG neurons and group IV muscle afferents were used in the present study, the probability that we recorded from DRG neurons/afferent fibres expressing insulin receptors was high.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…; Lázár et al . ). Hence, because small DRG neurons and group IV muscle afferents were used in the present study, the probability that we recorded from DRG neurons/afferent fibres expressing insulin receptors was high.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, we did not expressly identify whether insulin receptors were expressed in the DRG neurons and thin fibre muscle afferents from which we recorded. However, it has been reported that insulin receptors are expressed on DRG neurons in relatively high proportions (Baiou et al 2007;Lázár et al 2018), as well as peripheral nerves (Sugimoto et al 2002;Grote et al 2013). Moreover, insulin receptors are reported to be predominantly expressed in small nociceptive neurons (Baiou et al 2007;Lázár et al 2018).…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, electrophysiological, immunohistochemical and functional studies demonstrated the localization and functional significance of InsRs in primary sensory neurons (PSNs), in particular nociceptive PSNs expressing the transient receptor potential vanilloid type 1 (TRPV1) receptor [19][20][21][22][23][24][25]. The present review attempts to summarize experimental data on the diverse roles of insulin and InsRs in physiological and pathophysiological processes involving PSNs.…”
Section: Introductionmentioning
confidence: 99%